Negative Pressure Pulmonary Edema after Bilateral Nasal Packing following Transsphenoidal Pituitary Surgery for Nonfunctioning Pituitary Tumor - Singh, Apoorva; Mahajan, Shalvi; Aghi, Shweta; Kumar, Sanjay (Journal of Neuroanaesthesiology and Critical Care, 2023)
Negative pressure pulmonary edema (NPPE) is a well-known, albeit infrequent complication caused by upper airway obstruction. It may be seen after extubation following general anesthesia due to excessive negative intrathoracic pressure exerted against an obstructed upper airway. This leads to fluid extravasation from the pulmonary capillaries into the alveolar spaces and lung parenchyma. We report a case of NPPE after endoscopic transsphenoidal resection of the nonfunctional pituitary tumor, which occurred secondary to bilateral nasal packing. Reintubation and positive pressure ventilation were used to manage the patient, who was later extubated after the resolution of features of NPPE.
Keywords: transnasal transsphenoidal pituitary surgery; negative pressure pulmonary edema; nasal packing